2009
DOI: 10.1353/hpu.0.0185
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ Implicit and Explicit Attitudes About Race by MD Race, Ethnicity, and Gender

Abstract: Recent reports suggest that providers’ implicit attitudes about race contribute to racial and ethnic health care disparities. However, little is known about physicians’ implicit racial attitudes. This study measured implicit and explicit attitudes about race using the Race Attitude Implicit Association Test (IAT) for a large sample of test takers (N = 404,277), including a sub-sample of medical doctors (MDs) (n = 2,535). Medical doctors, like the entire sample, showed an implicit preference for White Americans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
168
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 370 publications
(199 citation statements)
references
References 70 publications
12
168
6
Order By: Relevance
“…Other studies have demonstrated general automatic racial biases among clinicians similar to that of the general population. 30,54 However, consistent with the present results, other studies of racial bias in pain perception and response have not found a relationship between traditional measures of general automatic racial evaluations and racial biases in pain perception. 33,64 Therefore, biases in pain perception may be more domain and/or stereotype-specific.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Other studies have demonstrated general automatic racial biases among clinicians similar to that of the general population. 30,54 However, consistent with the present results, other studies of racial bias in pain perception and response have not found a relationship between traditional measures of general automatic racial evaluations and racial biases in pain perception. 33,64 Therefore, biases in pain perception may be more domain and/or stereotype-specific.…”
Section: Discussionsupporting
confidence: 87%
“…A large survey employing the Implicit Association Task found the African American physicians did not show general automatic racial biases, where physicians of other races (European/White, Hispanic, and Asian) did reveal culturally congruent racial biases. 54 A patient-physician interaction study found that African American physicians display more positive non-verbal communication with African American patients than do European American physicians, though these researchers also found an ingroup bias among African American physicians such that they displayed fewer positive non-verbal behaviors when interacting with European American patients. 57 Prior research in non-physician samples has demonstrated that African Americans sometimes display general automatic biases against racial ingroup members, 52 particularly under certain circumstances (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…[39][40][41][42][43] Investigations of clinicians' ethnic and racial attitudes have shown that, similar to the general population, clinicians show little explicit or intentional bias but exhibit substantial bias in their implicit (unconscious) attitudes. [44][45][46] Theoretical models suggest that clinicians' implicit bias may affect their delivery of health care in 3 ways. 42,47,48 First, implicit bias may directly influence clinicians' decisions about their patients' medical treatment, with incorrect, often stereotypical assumptions leading to lower-quality care for minority than for white patients.…”
Section: Race/ethnicity Racism and Cvdmentioning
confidence: 99%
“…Our study is the first to demonstrate that >70% of the participating cardiologists associated strength and risk taking with men more than women. Prior studies have shown that the majority of physicians have implicit race/ethnicity bias at rates similar to community samples 12, 46, 51, 52, 53. Physicians may be especially vulnerable to the use of implicit biases in clinical settings characterized by time pressure, brief encounters, and the need to manage very complex situations—the type of situations in which implicit bias is more likely to be applied 17, 50.…”
Section: Discussionmentioning
confidence: 99%